Biological invasion of Pinus ponderosa and Pinus contorta: case study of a forest plantation in Northwestern Patagonia - Dezzotti, A.; Sbrancia, R.; Mortoro, A.; Monte, C. (Forest Systems, 2009)
In the Southern Hemisphere, Pinus species from plantations can bring about processes of biological invasion that cause significant and permanent changes on the structure and functioning of surrounding natural ecosystems. The invasive character of Pinus ponderosa (P) and Pinus contorta (C) was examined for a 20-year old plantation located in the Alicura Forest Station (40 degrees 40 minutes S and 71 degrees 00 minutes W), through the analysis of abundance, age and spatial structures, and dispersal of natural regeneration. Seedlings and saplings were located largely within the plantation boundaries, and exhibited a density of 6.9 ind/ha (41% for P and 59% for C), a clustered spatial pattern with clumps dispersed not randomly, and a mean dispersal rate of 9.5 m/yr for P. ponderosa and 5.4 m/yr for P. contorta. Both species were invading the adjacent area, according to technical criteria based on ecological responses. However, regeneration niche is strongly hindering tree establishment and dispersal, probably due to high plant cover, presence of vertic soils, and absence of ectomycorrhizal fungi. These results can contribute to predict the capability of P. contorta and P. ponderosa to become invasive, in order to maximize the positive balance of forestry based on these species in northwestern Patagonia.